Audit Komunikasi Media Sosial Instagram Kementerian PUPR @KEMENPUPR - Nurimansyah, Rafi; Ulhaq Bintoro, Muhammad Dafa; Ihsan At-Thariq, Muhammad; Rachmawati, Farikha (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
The Ministry of Public Employment and People's Housing (Kemen PUPR) won the award in the category of